2013
DOI: 10.1172/jci67284
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of ischemic brain damage by peritoneal dialysis

Abstract: Ischemic stroke is a devastating condition, for which there is still no effective therapy. Acute ischemic stroke is associated with high concentrations of glutamate in the blood and interstitial brain fluid. The inability of the tissue to retain glutamate within the cells of the brain ultimately provokes neuronal death. Increased concentrations of interstitial glutamate exert further excitotoxic effects on healthy tissue surrounding the infarct zone. We developed a strategy based on peritoneal dialysis to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…The deleterious effect of glutamate has been well documented in human stroke and in animal models of cerebral ischemia. In agreement with this, experimental studies from our research group have shown the beneficial effect on stroke outcome of glutamate uptake, mediated by glutamate transporters (Hurtado et al, 2008;Mallolas et al, 2006), or by its clearance using peritoneal dialysis (Godino et al, 2013).…”
Section: Glutamate Release and Microglia Activationsupporting
confidence: 76%
“…The deleterious effect of glutamate has been well documented in human stroke and in animal models of cerebral ischemia. In agreement with this, experimental studies from our research group have shown the beneficial effect on stroke outcome of glutamate uptake, mediated by glutamate transporters (Hurtado et al, 2008;Mallolas et al, 2006), or by its clearance using peritoneal dialysis (Godino et al, 2013).…”
Section: Glutamate Release and Microglia Activationsupporting
confidence: 76%
“…Severe renal impairment has certainly been linked to brain insults. Renal insufficiency may lead to an increase in serum glutamate and other excitotoxic substances in the blood [33] or intracranial hemorrhage following thrombolytic treatment for stroke [34]. We do not have cognitive outcomes in our study and we therefore cannot assess whether ACR or WMH are better predictors of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…55 Peritoneal dialysis is effective in removing glutamate, 55 and experimental evidence from animal models indicates that removal of glutamate by peritoneal dialysis can reduce infarct size and restore functional brain tissue. 56 …”
Section: Stroke In Patients Undergoing Haemodialysismentioning
confidence: 99%